Addressing disparities in European cancer outcomes: a qualitative study Protocol of the BEACON project - Ferraris, Giulia; Coppini, Veronica; Monzani, Dario; Grasso, Roberto; Kirac, Iva; Horgan, Denis; Pietrobon, Ricardo; Galvão, Victor; Pravettoni, Gabriella (Frontiers in Psychology, 2024)
Introduction: Health Ddisparities in cancer health represent a crucial factor in cancer survival rates, awareness, quality of life, and mental health of people receiving a cancer diagnosis and their families. Income, education, geographic location, and ethnicity are some of the most important characteristics impacting the healthcare divide underlying reasons for health disparities in cancer patients across Europe. Costs of healthcare, access to information, psycho-oncological support options, integration of cancer research and innovative care, and multidisciplinary cancer care teams are the main target areas when it comes to addressing disparities in the cancer context. As part of Cancer Carethe Beacon Project (BEACON), we developed a protocol for a qualitative study to explore and identify any relevant reasons for cancer inequalities and disparities in Europe. Methods: Our four stakeholders namely, cancer patients, healthcare providers, researchers, and policymakers will be recruited online, facilitated by collaborative efforts with cancer organizations from various European countries, including but not limited to Italy, Croatia, Estonia, and Slovenia. Reasons for disparities will be investigated from the perspective of four stakeholders, namely cancer patients, healthcare providers, researchers, and policymakers from different European countries part of the BEACON project. Qualitative online focus group discussions for each stakeholder will be conducted and transcribed. Subsequently, thematic analysis will be used to identify reasons and aspects that may contribute to the existing disparities in cancer outcomes at various levels of engagement and from different stakeholders' perspectives. Subsequently, analyses to ensure accuracy in matching their needs and preferences will be performed. Results from focus groups will inform a subsequent Delphi study and a SWOT analysis methodology. Discussion: Although advances in medical research, cancer screening, and treatment options are constantly progressing, disparities in access to and awareness of healthcare in cancer patients are even more noticeable. Thus, mapping the capacity and capability of cancer centres in the European Union, creating decision support tools that will assist the four stakeholders' information needs, and improving the quality of European cancer centres supporting European cancer centres in acquiring information related to accreditation and education will be the main objectives of the BEACON project.